Segmental extracellular and intracellular water distribution and muscle glycogen after 72-h carbohydrate loading using spectroscopic techniques - Shiose, Keisuke; Yamada, Yosuke; Motonaga, Keiko; Sagayama, Hiroyuki; Higaki, Yasuki; Tanaka, Hiroaki; Takahashi, Hideyuki (Journal of applied physiology (1985), 2016)
Body water content increases during carbohydrate loading because 2.7-4-g water binds each 1 g of glycogen. Bioelectrical impedance spectroscopy (BIS) allows separate assessment of extracellular and intracellular water (ECW and ICW, respectively) in the whole body and each body segment. However, BIS has not been shown to detect changes in body water induced by carbohydrate loading. Here, we aimed to investigate whether BIS had sufficient sensitivity to detect changes in body water content and to determine segmental water distribution after carbohydrate loading. Eight subjects consumed a high-carbohydrate diet containing 12 g carbohydrates·kg body mass(-1)·day(-1) for 72 h after glycogen depletion cycling exercise. Changes in muscle glycogen concentration were measured by (13)C-magnetic resonance spectroscopy, and total body water (TBW) was measured by the deuterium dilution technique (TBWD2O). ICW and ECW in the whole body (wrist-to-ankle) and in each body segment (arm, trunk, and leg) were assessed by BIS. Muscle glycogen concentration [72.7 ± 10.0 (SD) to 169.4 ± 55.9 mmol/kg wet wt, P < 0.001] and TBWD2O (39.3 ± 3.2 to 40.2 ± 3.0 kg, P < 0.05) increased significantly 72 h after exercise compared with baseline, respectively. Whole-body BIS showed significant increases in ICW (P < 0.05), but not in ECW. Segmental BIS showed significant increases in ICW in the legs (P < 0.05), but not in the arms or trunk. Our results suggest that increase in body water after carbohydrate loading can be detected by BIS and is caused by segment-specific increases in ICW.